Radiodont frontal appendages from the Fezouata Biota (Morocco) reveal high diversity and ecological adaptations to suspension-feeding during the Early Ordovician - Potin, Gaëtan J.-M.; Gueriau, Pierre; Daley, Allison C. (Frontiers in Ecology and Evolution, 2023)
The Early Ordovician Fezouata Shale Formation (485-475Ma, Morocco) is a critical source of evidence for the unfolding Great Ordovician Biodiversification Event (GOBE), the largest radiation in animal diversity during the Paleozoic. The Fezouata Shale preserves abundant remains of ancient marine organisms, including hundreds of specimens of radiodonts, a diverse and globally distributed group of stem lineage arthropods that first appeared as raptorial predators during the Cambrian Explosion. Frontal appendages are the most commonly preserved body parts of radiodonts at these sites, and their well-preserved anatomical characters are crucial for describing taxonomic diversity at the species level, while also providing essential data on mode of life, paleoecology, and feeding behaviour. A systematic review of Hurdiidae Lerosey-Aubril and Pates, 2018 radiodonts from the Fezouata Shale was performed using 105 specimens. The genus Pseudoangustidontus Van Roy and Tetlie, 2006 is recognised as a radiodont and ascribed to Hurdiidae, and a new second species of this genus is identified, Pseudoangustidontus izdigua sp. nov. Aegirocassis benmoulai Van Roy et al., 2015b is also reviewed and its diagnosis amended, with new details of differentiated endites in this appendage. The morphological similarity between both genera allows us to create Aegirocassisinae subfam. nov., which groups together the suspension-feeding hurdiids of the Fezouata Shale. Suspension-feeding radiodont appendages are more abundant than those of sediment sifting or raptorial radiodonts, with the Fezouata Shale showing the highest diversity of suspension-feeding radiodonts in the history of the group. This dominance and diversity of frontal filter-feeding appendages follows the "Ordovician Plankton Revolution", which started in the upper Cambrian and saw a huge radiation in plankton diversity.